Asset-based and asset-backed sukuk: structure and legitimacy - Md. Aminul Islam, Essia Ries Ahmed, Ramyar Rzgar Ahmed, Fathyah Hashim, (Opción, 2019)
The main objective of this study is to elucidate and describe the significance of the Asset Based and Asset Backed on Sukuk legitimacy. The analyzing data was obtained from Shariah pronouncements between the years 2005 to 2015. An analysis of the quantitative data was then made using the Partial Least Squares (PLS). The research found that asset-backed Sukuk have differed from asset-based Sukuk in regard to legitimacy, where the asset-backed Sukuk has a greater impact with regards to legitimacy than asset-based Sukuk. In conclusion, there is a positive relationship between the type of structure and Sukuk legitimacy.